Pengaruh Lingkungan Kerja, Teamwork Dan Kecerdasan Emosional Terhadap Kinerja Pegawai Dengan Variabel Mediasi Kepuasan Kerja Pada Pegawai Di Surabaya - Dinariyanti, Nurhaida; Iramani (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of work environment, teamwork, and emotional intelligence on employee performance, mediated by job satisfaction, within the Surabaya City Government. The objective is to analyse both direct and indirect relationships among these variables in the context of organizational efficiency policies. A quantitative cross-sectional design was applied using survey data from 156 employees, analysed through Structural Equation Modelling–Partial Least Squares (SEM-PLS). The results indicate that work environment and emotional intelligence significantly affect performance, while teamwork influences performance indirectly through job satisfaction. Job satisfaction partially mediates all relationships. These findings highlight the importance of contextual and psychological factors in improving public sector performance.